Digital Technology in English Language Learning - Thanga Judy, Joseph; Varadhan, Vishnu (Journal of Neonatal Surgery, 2025)
Through the application of information systems and specialized methods of thinking about problem-solving, the digital technologies curriculum helps students to become confident and creative developers of digital solutions. Students get a thorough awareness of digital systems, data, and information, as well as the processes involved in developing digital solutions, allowing them to play an active part in satisfying current and future needs. Children have a plethora of options to practice their English thanks to digital technologies. Children who grow up in a digitally enabling environment gain the abilities they will need for their future academics and vocations. Here are some excellent ways you and your child may practice English using technology together. As a result of the progress and application of information technology, education is one of the fields that is undergoing tremendous change. With the use of the latest channels and technology, mobile and e-learning are already facilitating the teaching and learning experience. Blended learning is a possible outcome of a learning system based on sophisticated technology. The appeal of a blended learning approach rests in the incorporation of technology-assisted learning approaches alongside traditional learning. By addressing the bad features of the conventional technique, technology has significantly improved the entire learning and teaching experience. A blended learning model for higher education is presented in this research..